Effect of pathogenic bacteria on a novel C-type lectin, hemocyte and superoxide dismutase/ alkaline phosphatase activity in Onchidium reevesii. Issue 102 (July 2020) - Liang, Wei; Wu, Rongyu; Yang, Tiezhu; Shen, Heding; Hu, Zhongjun
Abstract: Bacterial infection in the marine environment is a serious problem to maintain the stability of marine ecosystems. Nevertheless, there is little report so far for the biological effects of pathogenic bacteria in coastal ecosystems. Hence, we investigated the responses of shell-less Onchidium reevesii to resist against pathogenic bacterial infection. Analysis of data here could be used as fundamental information for assessment of innate immune response of O. reevesii . The full-length OrCTL cDNA was cloned and consists of 1849 base pair (bp) encoding protein of 192 amino acids. Constructing multiple alignments suggested that OrCTL has conserved carbohydrate recognition domain (CRD) of CTLs, containing an EPS (Glu-Pro-Ser) motif that may imply the function of recognition of carbohydrates like others invertebrate. OrCTL mRNAs were mainly detected in ganglion and hepatopancreas, and expression was highly up-regulated from 2 h after Vibrio harveyi challenge, rapidly decreased at 4 h, and significantly increased at 12 h. In addition, after challenge with Vibrio parahaemolytics, OrCTL gene expression was slightly up-regulated from 2 h, peaked at 12 h. Enzyme activity (in the hepatopancreas) and cell immune (in the hemolymph) were investigated along with Superoxide dismutase (SOD) activity, alkaline phosphatase (ALP) activity and cell cycle. SOD activities were significantly higher after V. harveyi and V. parahaemolytics challenge than that in the control group, respectively. By contrast, ALP activities were significantly inhibited after challenged with bacteria than that in the control group, respectively. Enzyme activities in the hepatopancreas obviously fluctuated, and ALP activity was more sensitive to bacteria. Cell responses illustrated that there were a significant higher percentage of cells in the S and G2/M phase in hemolymph after challenged with bacteria. Our results suggested that the immune response of O. reevesii could be activated by pathogenic bacteria, and the data will provide referent for the disease prevention of systematic investigation in aquatic animal. Highlights: We first cloned and identified the characteristic of OrCTL gene from O. reevesii. OrCTL mRNAs were mainly detected in ganglion and hepatopancreas. OrCTL mRNA level in hepatopancreas highly raised at 12 h after bacterial infection. SOD and ALP activities in hepatopancreas significantly fluctuated. The percentage of cells in the S and G2/M phase in hemolymph increased.